2008
DOI: 10.1002/adma.200703244
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Patterning of Organic Single‐Crystal Transistors from the Solution Phase

Abstract: Organic single‐crystal and polymer FET arrays can be fabricated using a novel solution‐based technique. The patterning of the organic semiconductor is achieved by semiconductor solution droplets selectively wetting the transistor electrode pads. The key advantages of the technique are the cleanliness of the patterning, the patterning speed, and the ultrasmall amount of material required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 21 publications
(19 reference statements)
1
78
0
Order By: Relevance
“…S7). In comparison, other patterning methods used to create patterned OSCs for isolated OTFTs have shown relative variances ranging from 20% to 84% (9,15,17,22,31,32,35,42,(48)(49)(50)(51)(52)(53)(54). For example, Li et al (15) have shown that using a PMMA:C8BTBT blend on a solution wetting pattern can deposit crystal plates that have a mobility relative variance of >40%.…”
Section: Resultsmentioning
confidence: 99%
“…S7). In comparison, other patterning methods used to create patterned OSCs for isolated OTFTs have shown relative variances ranging from 20% to 84% (9,15,17,22,31,32,35,42,(48)(49)(50)(51)(52)(53)(54). For example, Li et al (15) have shown that using a PMMA:C8BTBT blend on a solution wetting pattern can deposit crystal plates that have a mobility relative variance of >40%.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32] Patterning organic semiconductors reduces or eliminates parasitic current paths (crosstalk) between neighboring devices, and results in a significant decrease of the ''off'' current. [33][34][35] In the past decade, many techniques such as shadow masking, screen printing, inkjet printing, and softlithography have been developed to pattern organic semicon-REVIEW www.advmat.de ductor thin films, and this topic has been extensively reviewed. [36][37][38] However, compared to their thin-film counterparts, organic semiconductor single crystals have been patterned with limited success until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulties in device fabrication, organic single-crystal devices have been traditionally limited to fundamental charge-transport studies despite their superior performance and outstanding electrical characteristics. [35,39] Organic single-crystal FETs are usually fabricated by manual selection and placing of individual crystals, a tedious process for producing devices at high density and with reasonable throughput. [40] Recently, a patterning technique was reported that enabled direct deposition of large arrays of a wide range of organic single crystals onto prefabricated transistor source-drain electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…This method is useful in depositing crystals of small OS molecules that are otherwise difficult to form films. Furthermore, it is possible to have fine control over the crystallization conditions by choosing the initial concentration and host-liquid temperature [360,369].…”
Section: Patterned Deposition Os Crystalsmentioning
confidence: 99%